Analisa Perbaikan Tata Letak Penempatan Bahan Bakudi Area Gudang Penyimpanan - Beni Harma; Helga Ika Sudra (Jurnal Teknologi, 2020)
Activities carried out in the warehouse include material handling. Generally, the costs involved in material handling activities are quite large. One method that can be used in managing the layout of raw material placement in raw material warehouses is the class based storage method. Class based storage is a policy that divides storage into three classes A, B and C based on Pareto law. Pareto law is the principle of putting items that have the greatest accessibility near the Input-Output point. The distance of material handling to the initial layout raw material warehouse is 3,513,337 meters / month and the material handling costs are Rp. 134,534,765 / month, because the initial layout of the raw material warehouse still uses random storage and the raw materials that are widely used are not placed close to the intake floor of the production, so that the distance to get raw materials for production needs is far. After the re-layout design was made based on the placement of raw materials in the class based storage method, the material handling transfer distance was reduced to 2,644,459 meters / month and the material handling cost for the repair raw material warehouse layout fell to Rp. 99,949,520 / month. In other words, there was a decrease in material handling distance by 25% and material handling costs by 26%.